A Comparative Retro-Spective Study Between Excision Followed By Secondary Healing And Limberg’s Flap Surgery For Pilonidal Sinus (Indian Journal of Applied-Basic Medical Sciences, 2020)
Objective: The study was undertaken to compare the operative time, wound related complications,  hospital stay, wound healing time and rate of recurrence between the two techniques of pilonidal sinus  surgery. Methodology: This was a comparative retrospective study carried out at a tertiary care hospital  of patients operated from June 2017 to January 2019. 40 patients were studied who were equally divided  into 2 groups, Group A – excision followed by secondary healing group and Group B – Limberg’s flap group. Results: The outcomes were compared between both groups. In Group A, mean operative time  was 28.75 min while in Group B, it was 56.25min. In Group A, 6(30%) patients developed redness and  induration of the surrounding skin while in Group B, 2(10%) patients developed discharge from the  wound with surrounding redness followed by gaping and other 3(15%) patients had flap necrosis. In  Group A, mean hospital stay and wound healing time were 7.15 days and 31.75 days respectively while in  Group B, it was 5.75 days and 14.05 days respectively. In Group A, 2(10%) patients had recurrence during  the follow up period of 6 months while in group B there was no recurrence. Conclusion: Limberg’s flap surgery has significantly longer operative time and shorter wound healing time  as compared to the excision followed by secondary healing but there is no significant difference between  both techniques in terms of hospital stay, wound related complications or rate of recurrence. Limberg’s flap may be a good alternative to the secondary healing technique as it has lesser hospital stay  and lesser recurrence but a larger randomized study & long term follow up are required for definitive  conclusions and recommendation.
Keywords: pilonidal sinus; Limberg’ flap; hospital stay; operative time; recurrence